2013
DOI: 10.1016/j.brachy.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A phantom study to assess accuracy of needle identification in real-time planning of ultrasound-guided high-dose-rate prostate implants

Abstract: Factors limiting the accuracy of US-based needle reconstruction have been identified. Once recognized, these errors can be corrected for, resulting in accurate implant geometry. This facilitates a treatment technique combining excellent anatomic definition, minimal prostate motion, and accurate dose planning and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Published data on the clinical outcomes of HDRBT boost included patients treated with CT or MRI-based planning. Studies have shown the feasibility of ultrasound catheter tip localization compared with CT imaging [11,15]. To our knowledge, this is the first study to report early toxicity and PSA results of HDRBT boost using real-time TRUS-based planning, and the second to report dosimetric and clinical results of single-fraction HDRBT boost of 15 Gy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Published data on the clinical outcomes of HDRBT boost included patients treated with CT or MRI-based planning. Studies have shown the feasibility of ultrasound catheter tip localization compared with CT imaging [11,15]. To our knowledge, this is the first study to report early toxicity and PSA results of HDRBT boost using real-time TRUS-based planning, and the second to report dosimetric and clinical results of single-fraction HDRBT boost of 15 Gy.…”
Section: Discussionmentioning
confidence: 95%
“…Then, the sagittal mode is selected and catheters are pushed into the prostate to the bladder neck to ensure a good coverage of the prostate base ( Figure 1B). To know the exact position of the needle tip, a measurement of the needle lengths protruding beyond the template is performed ( Figure 1C) [11]. Once catheters are well positioned, three-dimensional TRUS images are acquired and prostate, anterior rectal wall and urethra are delineated by the radiation oncologist ( Figure 1D).…”
Section: High-dose-rate Brachytherapy Boost Treatmentmentioning
confidence: 99%
“…Two 3D printers could also simply be used. While real-time 3DUS planning and needle insertion guidance is expected to improve the efficiency of interstitial breast brachytherapy procedures, as it did for prostate cancer treatments [9], it remains to be tested through clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…3DUS systems [8] now offer, for the prostate, real-time planning and real-time guidance during insertion [9]. Furthermore, the potential of real-time 3DUS planning and catheter optimization for prostate cancer cases was demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation